(untitled) (Research, Society and Development, 2024)
The Odontogenic Keratocyst (OKC) is a lesion known for its high recurrence rate and its ability to infiltrate local tissues in the maxillary region. Objective: To analyze the efficacy of Carnoy’s solution as an adjunct therapy for OKC enucleation, aiming to provide updated information for academics and professionals in the field. Methodology: A literature review was conducted using scientific articles available in the Virtual Health Library (BVS) and PubMed, published between 2016 and 2023, addressing the use of Carnoy’s solution as an adjunct treatment for OKC. Discussion: There are studies that have indicated promising results with the use of Carnoy’s solution as an adjunct therapy for OKC in conjunction with the recommended surgical technique. Conclusion: This research provides a comprehensive view of the use of Carnoy’s solution as adjunct therapy in the treatment of odontogenic keratocyst, highlighting its accessibility and relatively low cost, making it an attractive option for oral surgeons in various clinical settings.